2004
DOI: 10.1158/1535-7163.417.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase (COX)-2-dependent effects of the inhibitor SC236 when combined with ionizing radiation in mammary tumor cells derived from HER-2/neu mice

Abstract: Cyclooxygenase (COX)-2-derived prostaglandins (PGs) are thought to contribute to tumor growth and resistance to radiation therapy. COX-2 protein expression is increased in many tumors including those of the breast. COX-2-derived PGs have been shown to protect cells from radiation damage. This study evaluated the role of COX-2-derived PG in radiation treatment by using the NMF11.2 mammary tumor cell line originally obtained from HER-2/neu mice that overexpress HER-2/neu. We determined whether the effects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…319 When combined with radiation or chemotherapy, COX-2 inhibitors have been found to promote DNA damage-induced cell killing of cancer cells. [320][321][322][323][324][325][326][327][328][329] A potential mechanism of sensitization of COX-2 inhibitors to DNA damaging agents may be that loss of COX-2 attenuates DNA repair. 322…”
Section: Cox-2mentioning
confidence: 99%
See 1 more Smart Citation
“…319 When combined with radiation or chemotherapy, COX-2 inhibitors have been found to promote DNA damage-induced cell killing of cancer cells. [320][321][322][323][324][325][326][327][328][329] A potential mechanism of sensitization of COX-2 inhibitors to DNA damaging agents may be that loss of COX-2 attenuates DNA repair. 322…”
Section: Cox-2mentioning
confidence: 99%
“…Because of its pro-inflammation activity, many pharmaceutical drugs have been developed to target COX-2 activity. , These inhibitors have been used in cancer treatment due to the frequent overexpression of COX-2 in cancer and to the strong link between inflammation and cancer . When combined with radiation or chemotherapy, COX-2 inhibitors have been found to promote DNA damage-induced cell killing of cancer cells. A potential mechanism of sensitization of COX-2 inhibitors to DNA damaging agents may be that loss of COX-2 attenuates DNA repair …”
Section: Targeting Cell Survival and Proliferation Pathwaysmentioning
confidence: 99%
“…Up-regulation of COX-2 after CXB administration has been observed prior to this study [ 52 ]. Higher COX-2 production may be stimulated via a negative feedback loop that was described previously [ 53 , 54 ]. Lombardi et al observed that temozolomide, one of the three chemotherapy agents available for the treatment of glioma, also causes increase of COX-2 level in glioma cells [ 55 ].…”
Section: Resultsmentioning
confidence: 98%
“…The mouse mammary tumor virus/c-Myc model was the first transgenic breast cancer mouse model reported in 1984, in which overexpression of the Myc transcription factor in the mammary gland resulted in spontaneous mammary adenocarcinomas [ 135 ]. However, MTV/ neu and HER2/ neu have been used in the literature to evaluate NSAIDs [ 136 , 137 ]. Celecoxib was again tested.…”
Section: Nsaids For Breast Cancermentioning
confidence: 99%
“…Animals were sacrificed when the tumors reached 20 mm in diameter or 15 months old. Celecoxib decreased tumor incidence and multiplicity, prolonged tumor latency, reduced lung metastasis, and PGI2 and PGE2 concentrations in mammary tumors and their adjacent mammary glands [ 137 ].…”
Section: Nsaids For Breast Cancermentioning
confidence: 99%